Aldo‐keto reductase family 1 member B10 is associated with hepatitis B virus‐related hepatocellular carcinoma risk. Issue 3 (11th May 2016) - Mori, Masashi; Genda, Takuya; Ichida, Takafumi; Murata, Ayato; Kamei, Masato; Tsuzura, Hironori; Sato, Shunsuke; Narita, Yutaka; Kanemitsu, Yoshio; Ishikawa, Sachiko; Kikuchi, Tetsu; Shimada, Yuji; et al.
Abstract : Aim: Recent reports have indicated that aldo‐keto reductase family 1 member B10 (AKR1B10), a cancer‐related oxidoreductase, was upregulated in some chronic liver diseases. However, few studies have reported AKR1B10 expression in chronic hepatitis B virus (HBV)‐infected patients. The aim of the present study was to analyze AKR1B10 expression and its relevance on hepatocellular carcinoma (HCC) development in patients with chronic HBV infection. Methods: Expression of AKR1B10 in the liver of 119 chronic HBV‐infected patients was assessed and quantified immunohistochemically. A multivariate Cox model was used to estimate the hazard ratios of AKR1B10 expression for HCC development. The cumulative incidences of HCC were evaluated using Kaplan–Meier analysis. Results: Expression of AKR1B10 in the study cohort ranged from 0% to 84%. During the median follow‐up time (6.2 years), 13 patients developed HCC. Multivariate analysis revealed that high AKR1B10 expression (≥15%) was an independent risk factor for HCC (hazard ratio, 10.8; 95% confidence interval, 3.0–38.6; P  < 0.001). The 5‐year cumulative incidences of HCC were 20.6% and 2.6% in patients with high and low AKR1B10 expression, respectively ( P  < 0.001). Patients with high AKR1B10 expression had significantly higher alanine aminotransferase levels during follow‐up than those with low expression, even though antiviral treatment decreased HBV‐DNA levels in both groups. Conclusion: Chronic HBV‐infected patients with high hepatic AKR1B10 expression had an increased risk of HCC development. This suggests that AKR1B10 upregulation might play a role in the early stages of HBV‐related hepatocarcinogenesis.